THE REFLECTION OF ISLAMIC BANKING IN THEORY AND PRACTICE - Anis Mashdurohatun (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
This study aims to identify the struggle of Islamic Banking in theory and practice, analyzes the factors that affect the implementation of Islamic banking as well as the reformulation of Islamic banking in the future. This study used sociological juridical approach, and the data used were primary and secondary data, these data were then analyzed by using descriptive analytical. The results showed that Islamic banking has an important principles la riba, la misyir, la gharar, la Dzulm and la haram within the framework of basic fairness, balance and well-being, but in practice there are still aberrations on Islamic principles. Some factors affect the strength of the capitalist system are human resources and culture of capitalism in banking practices and lack of oversight and enforcement. Islamic banking solution in the foreseeable future need to be strengthen the Islamic banking system, Human Resources who are experts in sharia and revitalizing the Islamic principles of independent, separate from the frame ta'awun capitalist system, improve internal and external monitoring and enforce the principle of sharia (kafah) in whole, consistent (Istiqomah) and giving sanctions as tarbiyah. Keywords: Reflection, Islamic banking, theory and practice.